Catalog of Lung Cancer Gene Mutations Among Chinese Patients - Xue, Xinying; Asuquo, Idorenyin; Hong, Lei; Gao, Jie; Dong, Zhouhuan; Pang, Li; Jiang, Tianjiao; Meng, Mingming; Fan, Jingbo; Wen, Jiaxin; Deng, Hui; Zang, Xuelei; et al. (Frontiers in Oncology, 2020)
Background: Detailed catalog of lung cancer-associated gene mutations provide valuable information for lung cancer diagnosis and treatment. In China, there has never been a wide-ranging study cataloging lung cancer-associated gene mutations. This study aims to reveal a comprehensive catalog of lung cancer gene mutations in china, focusing on EGFR, ALK, KRAS, HER2, PIK3CA, MET, BRAF, HRAS, and CTNNB1 as major targets. Additionally, we also aim to correlate smoking history, gender, and age distribution, and pathological types with various types of gene mutations. Patients and Methods: A retrospective data acquisition was conducted spanning 6 years (2013-2018) among all patients who underwent lung cancer surgeries not bronchial or percutaneous lung biopsy at three major tertiary hospitals. Finally, we identified 1729 patients who matched our inclusion criteria. Results: 1081 patients（62.45%） harbored EGFR mutation. ALK (n=42, 2.43%), KRAS (n=201,11.61%), CTNNB1 (n=28, 1.62%), BRAF (n=31, 1.79%), PIK3CA (n=51, 2.95%), MET (n=14, 0.8%), HER2 (n=47,2.72%), HRAS (n=3, 0.17%) and other genes(n=232, 13.4%) . Females expressed 55.35% versus males 44.65% mutations. Among subjects with known smoking histories, 32.82% smokers, 67.18% nonsmokers were observed. Generally, 51.80% patients were above 60 years versus 48.20% in younger patients. Pathological types found includes LUADs 71.11%, SQCCs 1.68%, ASC 0.75%, LCC 0.58%, SCC 0.35%, ACC 0.17%, and SC 0.06%. Conclusion: We offer a detailed catalog of the distribution of lung cancer mutations. Showing how gender, smoking history, age, and pathological types are significantly related to the prevalence of lung cancer in China.